Impacts of hydroxylation on the photophysics of chalcones: insights into the relation between the chemical composition and the electronic structure. Issue 13 (20th March 2018) - Kalchevski, Dobromir A.; Petrov, Vesselin; Tadjer, Alia; Nenov, Artur
Abstract : A computational study of the photochemistry and photophysics of hydroxylated chalcones is presented which rationalises discrepancies in linear absorption spectra. Abstract : A combined theoretical/experimental study of the photoreactivity of two flavylium-derived chalcones, 2, 4, 4′-trihydroxychalcone and 2, 4′-dihydroxychalcone, at the multiconfigurational wavefunction level of theory (CASSCF//CASPT2) in vacuo and in an implicit solvent (water, treated as a polarisable continuum) and by means of linear absorption spectroscopy is presented. The photosensitivity of flavium salts is expressed in the ability of their chalcone form to undergo a cis – trans isomerisation which has found application in logical networks. Despite a considerable amount of experimental data documenting the dependence of the isomerisation on solvent, pH and temperature, the knowledge of how chalcones process energy under various conditions at the molecular level is still scarce. On the example of 2, 4, 4′-trihydroxychalcone we unravel the complex excited state deactivation mechanism in vacuo involving ultrafast decay through conical intersections, formation of twisted intramolecular charge transfer species, intramolecular proton transfer and inter system crossings. Furthermore, we rationalise the observed discrepancies in the linear absorption spectra of 2, 4, 4′-trihydroxychalcone and 2, 4′-dihydroxychalcone, thereby establishing a link between the functionalisation pattern and the observed spectral properties.